Circulating pig‐specific DNA as a novel biomarker for monitoring xenograft rejection. (11th May 2019) - Zhou, Ming; Lu, Ying; Zhao, Chengjiang; Zhang, Junfang; Cooper, David K. C.; Xie, Chongwei; Song, Zongpei; Gao, Hanchao; Qu, Zepeng; Lin, Shan; Deng, YangYang; Hara, Hidetaka; et al.
Abstract: Monitoring for immune rejection is crucial for long‐term survival of pig xenografts. Circulating DNA is a promising non‐invasive biomarker for either organ injury or response to therapy. In this study, circulating pig‐specific DNA (cpsDNA) was monitored during xenograft rejection. Potential targets of cpsDNA were selected by in silico analysis, and species specificity of selected primers was confirmed by PCR. Subsequently, cpsDNA as a biomarker was evaluated using a complement‐dependent cytotoxicity (CDC) assay in vitro. Then, early diagnosis and response to rapamycin were assessed by an in vivo imaging model of pig‐to‐mouse cell transplantation. Finally, cpsDNA was monitored in a pig‐to‐monkey artery patch transplantation model. The results showed that (a) a method of cpsDNA quantitation was established for application in mouse and nonhuman primate models; (b) cpsDNA reflected CDC in vitro; (c) cpsDNA in vivo mirrored xenograft rejection, and correlated with xenograft loss in pig‐to‐mouse cell transplantation; (d) cpsDNA was significantly reduced when rapamycin was administered; and (e) dynamic cpsDNA was detectable in pig‐to‐monkey artery patch transplantation. In conclusion, measurement of cpsDNA could prove to be a less invasive, but more specific and sensitive low‐cost biomarker enabling monitoring of xenograft rejection and the response to immunosuppressive therapy.